Militarizált szex: katonák, prostitúció, nemi betegségek a Nagy Háborúban - Forrai, Judit (Per Aspera ad Astra, 2018)
Since ever, it was a serious problem of military leaderships to manage the soldiers’ sexual demands and practice, generally speaking, their relationship with women and as a consequence to treat the sexually transmitted infectious diseases. It was a serious problem especially in prolonged campaigns. In all kind of warfare, there is a close tripartite interrelation of sex, prostitution and venereal diseases among the military personnel. Nevertheless managing them as a complex issue shows a wide range of varieties in specific historic periods. The military way of thinking and policy do definitely not resemble the circumstances, expectations and paradigms of the usual civil life-style. Military tasks and law enforcement are more rigorous than the civil ones for the tasks to be achieved are commended, typically in a relentless way and controlled continuously. Stages of development, movements, steps and commandments presented here indicate clearly the eternity of this topic and a wide range of solutions, depending on the actual historic era of sciences, politics, and behavioural patterns. The Great War induced substantial changes in the military way of thinking. In the wake of spreading sexually transmitted diseases, there were established field brothels by the military supply system with painstaking regulations. The present study shows the history of these facilities.